YOUTH MEDIA IMAGINARIES IN PALESTINE: A HERMENEUTIC EXPLORATION - Asthana, Sanjay; Havandjian, Nishan Rafi (European Scientific Journal, ESJ, 2014)
A primary purpose of our paper is to demonstrate how young people in refugee camps in Palestine appropriate and reconfigure old and new media in the process of creating personal and social narratives. Focusing on Palestinian identity and selfhood, the project explores how and in what specific ways, children and young people engage with media forms to express their ideas of politics, citizenship, and democratic participation. The paper shall examine three Palestinian youth initiatives as case studies that span various media – magazines, radio, photography, video, and the new media – particularly the multiple uses of the Internet. Drawing insights from postcolonial and feminist epistemologies, media and cultural studies, certain strands of media education scholarship, the paper shall probe the issues through a set of inter-related questions. What are the salient features of the Palestinian youth media practices? What kinds of media narratives are produced and how do these relate to young people’s notions of identity and selfhood? How do young people refashion the notion of the political? What do these media practices mean in Arab cultural contexts and settings? The researchers paid a visit to the Palestinian Territories and Haifa Israel to meet with youth media leaders and interview youth media writers.